Spirit of Entrepreneurship in Islamic Higher Education - Hendrianto, Hendrianto; Ilhamiwati, Mega; Monica, Fina; Lestari, Ratna (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: This research aims to analyze the meaning, management, impact of implementation, and formulate ideas for developing entrepreneurship in the Sharia Economics Study Program at IAIN Curup.Design/Method/Approach: This field research uses a qualitative descriptive approach. The primary data sources in this research are the chairman, secretary, Sharia Economics Study Program staff, and HMPS Sharia Economics students. The data collection techniques used is observation, interviews and documentation. Meanwhile, data analysis techniques go through the stages of reading all the data, compiling data, knowing general patterns of data, grouping data, conclusions, and triangulation.Findings: The research results show that students see entrepreneurship as creating, developing and managing businesses for profit. Preparation for business, characteristics of entrepreneurs and ICT are also important. Meanwhile, success can be seen from profits, achieved goals, business development, customer satisfaction and product consistency. Students run the Nurulillah Shop entrepreneurial business with facilities and funding from the study program and HMPS, integrating ICT in promotions, and managing time and business management with group strategies. The application of entrepreneurship has an impact on increasing knowledge and skills, motivation, benchmarks for facing business challenges, financial independence, and developing relationships that support the development of entrepreneurship. The development idea formulated is called Entrepreneurial Prosperity, namely to achieve success in entrepreneurship through product development, science and technology, partners, support, awards and mentorship.Originality/Values: contribution to this research is to see the spirit of Sharia Economics students in entrepreneurship in the IAIN Curup environment